PENGARUH FORTIFIKASI SARI KACANG HIJAU DENGAN PEMANIS STEVIA TERHADAP KARAKTERISTIK ORGANOLEPTIK DAN TINGKAT KESUKAAN MINUMAN YOGURT - Fitri Yuliani; Kiki Rizki Handayani (Sekolah Tinggi Ilmu Kesehatan Madani Yogyakarta, 2025)
Fortification of mung bean (Vigna radiata) extract aims to enhance the nutritional content of yogurt. However, the distinctive sour taste of mung bean yogurt is often less preferred by consumers; therefore, stevia, a natural sweetener, was added to improve its flavor. This study aimed to evaluate the effect of mung bean extract fortification on the organoleptic characteristics and consumer preference of yogurt drinks, as well as to determine the formulation that meets acceptable pH and total titratable acidity (TTA) standards. Four yogurt formulations were prepared with different concentrations of mung bean extract: 0% (F1), 30% (F2), 60% (F3), and 90% (F4). The samples were analyzed for organoleptic properties, consumer preference, pH, and TTA. Data were analyzed using SPSS software. The results showed that the addition of mung bean extract significantly affected the aroma, taste, and viscosity of yogurt. Increasing concentrations of mung bean extract reduced consumer preference for aroma and taste. The pH values of fortified yogurts ranged from 3.73 to 4.42, while TTA values ranged from 0.16 to 0.95. Overall, the 30% mung bean extract formulation (F2) achieved the most favorable balance, with neutral preference scores and acceptable acidity levels.